The Antibacterial Activity of LL-37 against Treponema denticola Is Dentilisin Protease Independent and Facilitated by the Major Outer Sheath Protein Virulence Factor - Rosen, Graciela (American Society for Microbiology, 2012)
Host defense peptides are innate immune effectors that possess both bactericidal activities and immunomodulatory functions. Deficiency in the human host defense peptide LL-37 has previously been correlated with severe periodontal disease. Treponema denticola is an oral anaerobic spirochete closely associated with the pathogenesis of periodontal disease. The T. denticola major surface protein (MSP), involved in adhesion and cytotoxicity, and the dentilisin serine protease are key virulence factors of this organism. In this study, we examined the interactions between LL-37 and T. denticola. The three T. denticola strains tested were susceptible to LL-37. Dentilisin was found to inactivate LL-37 by cleaving it at the Lys, Phe, Gln, and Val residues. However, dentilisin deletion did not increase the susceptibility of T. denticola to LL-37. Furthermore, dentilisin activity was found to be inhibited by human saliva. In contrast, a deficiency of the T. denticola MSP increased resistance to LL-37. The MSP-deficient mutant bound less fluorescently labeled LL-37 than the wild-type strain. MSP demonstrated specific, dose-dependent LL-37 binding. In conclusion, though capable of LL-37 inactivation, dentilisin does not protect T. denticola from LL-37. Rather, the rapid, MSP-mediated binding of LL-37 to the treponemal outer sheath precedes cleavage by dentilisin. Moreover, in vivo, saliva inhibits dentilisin, thus preventing LL-37 restriction and ensuring its bactericidal and immunoregulatory activities.